Opportunism as a firm and managerial trait: Predicting insider trading profits and misconduct - Ali, Usman; Hirshleifer, David (Journal of Financial Economics, 2017)
We show that opportunistic insiders can be identified through the profitability of their trades prior to quarterly earnings announcements (QEAs) and that opportunistic trading is associated with various kinds of firm or managerial misconduct. A value-weighted trading strategy based on (not necessarily pre-QEA) trades of opportunistic insiders earns monthly four-factor alphas of over 1%, which is much higher than in past insider trading literature and substantial and significant even on the short side. Firms with opportunistic insiders have higher levels of earnings management, restatements, US Securities and Exchange Commission enforcement actions, shareholder litigation, and executive compensation. These findings suggest that opportunism is a domain-general trait.